COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCEBANKING REGISTERED ON THE INDONESIA STOCK EXCHANGE (PERIOD 2012-2016) - Novita Setiani; V. Titi Purwantini (AKTUAL, 2018)
The research aims to analyze the financial performance of Government Bank and Private Bank and to determine whether there are differences between the financial performance of Government Banks and the Private Bankregistered on the Indonesia stock exchange (period 2012 to 2016).The population in this research is Government Bank and the Private Bank in Indonesia as many as 42 banks. While 4 Goverment Bank and 4 Private Bank registered on the Indonesia stock exchangewere research samples.Financial ratio indicators measured byLoan to Deposit Ratio (LDR) ,Operational Cost/Operational Income (BOPO) and Net Intererest Margin (NIM).Analysis methods that used is Paired Sample Test.Result from this research are not significant different between Government Bank and Private Bank reviewed from financial ratio LDR, there are significant different between Government Bank and Private Bank reviewed from financial ratio BOPO and NIM.Keywords : Finantial Ratio, Loan to Deposit Ratio (LDR) .Operational Cost/Operational Income (BOPO) and Net Intererest Margin (NIM)